Students' learning approaches to enhance teaching delivery — Bridging the gaps between learning and teaching in Universiti Teknologi MARA (UiTM) : A case study of UiTM Sarawak / Senian Malie ... [et al.] - Malie, Senian; Akir, Oriah; Omar, Noraida (2010)
Different learning approaches, learning methods and learning environments are believed to have different effects on students' academic performance (Fuller, 1999; Biggs, Kember and Leung, 2001). Studies have also revealed that students use different learning approaches and strategies and these in turn influence their academic achievement. However, students' learning approaches and strategies are not the sole factors that impact their academic achievement. Other determinants such as learning methods and learning environments may also surface (Jarvis and Woodrow, 2001). The aims of this research are three-folds: to determine the learning approaches most favoured by students and the impact of the learning approaches on their academic performance; to examine the learning methods most preferred by students; and to identify the learning environments most desired by students — in their quest to achieve excellent academic performance. The research uses Biggs, et al (2001) 2021 item Revised-Two-Factor Study Process Questionnaire (R-SPQ-2F), and adapted Jarvis et al (2001) six constructs to measure students' learning method and five on learning environment as modified by Wishart (2005).